Diagnosis dan Tatalaksana Terkini Oftalmopati Graves : Sebuah Tinjauan Pustaka - Nurannisa, Isma Ayu; Mulyani, Nanik Sri (Syntax Literate, 2025)
Graves' ophthalmopathy is an autoimmune disease with major involvement in extraocular and orbital muscles. Graves' ophthalmopathy is one of the most common extrathyroid symptoms in Graves' disease. This review aims to provide the latest reference on graves ophthalmopathy, including the diagnosis approach and appropriate management to provide an understanding so that it can reduce the incidence of worsening of the condition in the future. Literature searches were conducted using databases such as PubMed, Science Direct, and Google Scholar in the period 2020-2024 with the keywords "Graves Ophthalmopathy", "Thyroid Eye Disease", "Diagnosis" and "Treatment". The diagnosis of ophthalmopathy can be established if there is immune-related thyroid dysfunction, signs of abnormalities in the eyes and radiological evidence of fusiform enlargement of the tendons in one or more extraocular muscles. The classification of OG can be based on clinical activity and severity. Treatment of OG can be done based on the severity so that treatment from the beginning must be carried out immediately to avoid severe severity that can threaten vision.